"Cattle dung biochar-packed vertical flow constructed wetland for nutrient removal": Effect of intermittent aeration and wastewater COD/N loads on the removal process. (October 2021) - Chand, Naveen; Kumar, Kapil; Suthar, Surindra
Abstract: The effect of varying COD/N ratio (1:1, 3:1, 5:1, 8:1, 10:1) of wastewater and intermittent aeration on treatment efficiency of biochar (BC)-packed (with 10% V/V biochar) vertical flow constructed wetland (VFCW), planted with Colocasia esculenta was assessed in this study. Three setups of VFCW were prepared in two sets: aerated (with an airflow rate of 1.0 ± 0.6 L min −1 for 6 h d −1 ) and non-aeration, and changes in COD, NH4 + -N, NO3 -N, TN, and TP (total phosphorous) in the effluent was investigated. In VFCWS with intermittent aeration, COD, NH4 + -N, NO3 -N, TP removal was 99.0, 97.0, 81.0, and 89.0%, significantly higher ( p  < 0.05) than non-aerated VFCW setups as 91.3, 70.9, 86.97 and 64.4%, respectively. In non-aerated VFCWs, BC addition in combination with plantation was advantageous in the nutrient removal process than setups without BC. COD/N ratio of wastewater did not show a significant impact on the working of VFCWs if amended with BC and intermittent aerations, suggesting slow adsorption rate and fast aerobic degradation of organic matter. The study suggests that oxygen supply management and BC addition in VFCWs could be an effective strategy to treat wastewater with a high organic load. Apart from that study results will be useful for refinement of the operational strategy with varying organic load. Highlights: Intermittent aeration and biochar addition improved the functioning of VFCW. High COD (99.0%), NH4 + -N (97.0%), NO3 -N (87.0%) and TP (89.0%) were achieved. Wastewater with a high organic load could be treated with facilitated VFCWs. The incorporation of multiple strategies in VFCWs improved the removal process.